Электрофизические характеристики грунта в местах расположения энергообъектов Украины - Колиушко, Денис Георгиевич; Руденко, Сергей Сергеевич; Колиушко, Георгий Михайлович (НТУ "ХПИ", 2015)
На основании анализа результатов зондирования получено статистическое распределение слоистости грунтов в местах расположения энергообъектов Украины, разработаны рекомендации о применимости метода эквивалентирования многослойных геоэлектрических структур при определении нормируемых параметров заземляющих устройств. Доказана необходимость создания математической модели заземляющего устройства, расположенного в трехслойном грунте, а также новой установки для зондирования грунта, позволяющей увеличить глубину зондирования, и средств интерпретации.

Purpose. Definition of the direction for further research to improve accuracy of the calculation of rated parameters of ground grids based on the analysis of statistical databases of electrophysical characteristics of the soil. Methodology. To solve this problem we compiled the statistical base of soil of Ukraine in the location of electrical substation, we performed the statistical analysis for the number of layers of geoelectric structure, and electrical characteristics. In the experiments implemented the comparing of accuracy calculation of the most typical three-layer soil in the Ukraine, by the new three-layer model of ground grids and the equivalent two-layer model, which used previously. Results. On the results of analysis the ranges of the electrical resistivity and statistical distribution for electro-physical characteristics of the soil are determined. The resulting distributions allow to develop criteria for instruments, installations and means of interpretation during the sounding of soil, as well as the requirements for mathematical models of ground grids.
Analysis of electrophysical characteristics of grounds in the vicinity electrical substation of Ukraine
Keywords: заземляющее устройство; электроустановки; электромагнитная диагностика; трехслойная геоэлектрическая структура; вертикальное электрическое зондирование; энергообъекты; three-layer geoelectric structure; vertical electrical sounding; ground grids; soil; substation